Coupled effects of environmental conditions on the spatio-temporal variability of phytoplankton in canyon-shaped reservoirs. (1st February 2023) - Liao, Ning; Li, Hong; Zhang, Linglei; Chen, Min; Li, Jia; You, Lihua
Abstract: Algal blooms are increasingly frequently reported in reservoirs, posing a serious threat to the water environment and operation status. The phytoplankton that causes blooms is affected by environmental conditions including light-heat, water quality and hydrodynamics. Exploring the environmental coupling effects (including hydrodynamic effects) of phytoplankton is critical for reservoir management, but such studies are still scarce. This study monitored the phytoplankton and environmental factor data of Zipingpu Reservoir for 29 months and constructed a novel partial least squares structural equation modeling to quantify the impacts of environmental conditions on the phytoplankton in the canyon-shaped reservoir. There were significant spatial differences in the biomass of phytoplankton in the reservoir, and the biomass reached its peak in May to July every year. The model explained 51.4% of the spatiotemporal variation in phytoplankton and revealed that the coupling effect of flow and nutrition affected the transparency (with a coefficient of −0.427, p < 0.01) and then influence the biomass of phytoplankton. The coupling effect of flow and meteorology indirectly modified phytoplankton biomass by changing physicochemical properties (with a coefficient of 0.261, p < 0.01). Meteorology indirectly affected stratification by changing the physicochemical properties of the water and promoted temporal variation in phytoplankton biomass. The contribution rates of hydrodynamic conditions, including operation, flow and stratification variables, to phytoplankton dynamics were extremely high, reaching 34.9%. The flow change caused by reservoir operation will significantly affect phytoplankton (with a coefficient of 0.352, p < 0.01), especially when the temperature is appropriate, and a hydrodynamic operation strategy aiming to avoid rapid increases in the water level (more than 0.8 m d −1 ) in the reservoir may be effective in restraining blooms. This study not only further clarifies the coupling effects of environmental conditions on phytoplankton, but also provided important information to support sustainable blooms prevention and control decisions by reservoir managers. Graphical abstract: Image 1 Highlights: The proposed structure equation model explained 51.4% of phytoplankton variation. Coupling effect of hydrodynamic conditions has the highest explanation rate of 34.9%. Water level rapid rise during the suitable temperature period promoted algal blooms. Flow-depended nutrients and transparency features dominated to the spatial variation. Temperature-driven thermal stratification results in the temporal variation pattern.